If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (5x + -6) + 21 Reorder the terms: x = (-6 + 5x) + 21 Remove parenthesis around (-6 + 5x) x = -6 + 5x + 21 Reorder the terms: x = -6 + 21 + 5x Combine like terms: -6 + 21 = 15 x = 15 + 5x Solving x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. x + -5x = 15 + 5x + -5x Combine like terms: x + -5x = -4x -4x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -4x = 15 + 0 -4x = 15 Divide each side by '-4'. x = -3.75 Simplifying x = -3.75
| 23X-5X^2=-24 | | 4.6=5.8-p | | -(-3-7g)-11=-9-5g | | 6x^2-73x-63=0 | | 3[x-3]+2=13-x | | 3a+7(5a+7b)-10(3+5b)=14ab+50(3+4) | | 2[3x+2(x-2)]+19=(3x+1)*2 | | 8x+3-(7+9x)=-8 | | 2(3c+2d)-2(5c-3d)= | | -(3y-1)-3y+7=2 | | 2x^3-11x^2-x+5=0 | | 3(x+2)=5(3x-2) | | y=x^4-2x^3-3x^2 | | y=80x-5x^2+2 | | 24x+x^2=-1 | | ln(x/(x-9)) | | 3x+ky=25 | | (2x+4)2=25 | | (8x-5)+1=9(x+5) | | 31x^2+5=0 | | x+-7=-6 | | [8x-5]+1=9[x+5] | | ae-yd=y*y | | (-3x-6)(x-1)=0 | | a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 |